1999
DOI: 10.1039/a900758j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of lead hydroxyapatite particles using acetamide

Abstract: Lead hydroxyapatite (PbHAP) particles were prepared by a homogeneous precipitation reaction of Pb(NO 3 ) 2 and (NH 4 ) 2 HPO 4 using acetamide (AA) in aqueous media. The particles obtained under different conditions were examined by various methods, including XRD, FTIR, SEM, ICP, TG-DTA and N 2 adsorption. The crystal phase of the products depended on the concentration of AA ([AA]) and the ageing period (t a ). Large highly crystalline needle-like PbHAP particles were formed by ageing at [AA]=0.4-1.6 mol dm−3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In the apatite structure, the Ca ions occupy two types of nonequivalent sites: the M (1) sites are at the fourfold symmetry 4(f) position and the M(2) sites are at the sixfold symmetry 6(h) position [2]. The apatite structure has a high flexibility, so many metal ions can be incorporated into the structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the apatite structure, the Ca ions occupy two types of nonequivalent sites: the M (1) sites are at the fourfold symmetry 4(f) position and the M(2) sites are at the sixfold symmetry 6(h) position [2]. The apatite structure has a high flexibility, so many metal ions can be incorporated into the structure.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic Ca-HA has attracted our attention for its utility in the fields of bioceramics, catalysts, adsorbents, and so on [1].…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic Ca-HAp has attracted our attention for its utility in the fields of bioceramics, catalysts, adsorbents, and so on [1].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, CaHap is widely applied for separating various proteins using as a column for a high-performance liquid chromatograph (HPLC) apparatus and many essential studies have been reported 2,6,8 . The CaHap structure is so tolerant to ionic substitutions, there are many reports of the occupying of Ca sites by various divalent (Ca(II), Mn(II), Mg(II), Sr(II), Cd(II), Pb(II) and Ba(II)) [9][10][11][12][13][14][15][16] , trivalent (Al(III), Fe(III)) 17 and also tetravalent cations (Ti(IV)) 18 . It is also possible to exchange PO4…”
Section: Introductionmentioning
confidence: 99%